Perbanyakan in vitro tanaman kina (Cinchona ledgeriana Moens) melalui tunas aksiler dan apikal In vitro propagation of cinchona (Cinchona ledgeriana Moens) from axillary and apical buds - Imron RIYADI; J. S. TAHARDI TAHARDI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2009)
AbstractThe use of the appropriate source of nodalbud explants in culture can increase theeffectiveness and efficiency of shootmultiplication. An experiment was conducted todetermine and compare the rate of in vitro shootmultiplication from apical and axillary budsin cinchona (Cinchona ledgeriana Moens) andtheir subsequent growth and development. Theplant material used was Cinchona ledgerianaoriginating from the Indonesian Tea andCinchona Research Institute, Gambung, WestJava. Explants were taken from apical andaxillary nodes from in vitro germinated seedlings.The cultures were incubated at 26 0 C and 60%relative humidity under a 14-h photoperiod withlight intensity of 30 µmol photon/m 2 /sec.provided by cool-white fluorescent tubes (TL40 W) for 4 - 8 weeks. The parameters observedwere shoot multiplication rate, shoot growth anddevelopment such as shoot length, leaf numberand rooting frequency. Apical and axillary nodesproduced shoots at different multiplication rateson Murashige-Skoog (MS) standard mediumcontaining 30 g/L sucrose and supplemented with1 – 5 mg/L BA in combination with 0.1 mg/L IBA.Furthermore, shoots or plantlets of cinchonagrew and developed on the same mediacontaining 5 – 10 mg/L IAA combined with0.5 mg/L IBA. The results showed that shootmultiplication rate was higher in axillary than inapical nodes. The highest multiplication rate inaxillary nodes was 24.6 shootlets with 3 mg/LBA treatment, whereas in apical nodes it was17.2 shootlets with 5 mg/L BA treatment for eightweeks. The highest rooting frequency ofcinchona plantlet was 90%, achieved with 5 mg/LIAA in combination with 0.5 mg/L IBA. Theplantlets were successfully acclimatized andtransplanted to the fieldAbstrakSumber eksplan berupa nodus/tunas padakultur in vitro umum digunakan untuk multi-plikasi tunas. Penelitian ini bertujuan untukmembandingkan tingkat multiplikasi antara tunasapikal dengan tunas aksiler tanaman kina Ledgersecara in vitro. Bahan tanaman yang digunakanadalah kina Ledger (Cinchona ledgeriana Moens)yang berasal dari Pusat Penelitian Teh dan Kina,Gambung, Jawa Barat. Eksplan berupa nodus/tunas apikal dan aksiler asal biji yang dikecam-bahkan secara in vitro. Kultur tersebut diinku-basikan dalam ruang terang pada intensitascahaya 30 μmol foton/m 2 /detik dengan periodepenyinaran 14 jam pada suhu 260 C dankelembaban relatif + 60% selama 4 – 8 minggu.Parameter yang diamati adalah perbandinganmultiplikasi tunas dan pertumbuhan tunas yangmeliputi rata-rata tinggi tunas, jumlah daun danfrekuensi pengakaran. Nodus apikal maupunaksiler menghasilkan tunas dengan tingkatMurashige-Skoog (MS) standar yang me-ngandung sukrosa30 g/L dan ditambahkan BA1 – 5 mg/L dikombinasikan IBA 0,1 mg/L.Selanjutnya tunas/planlet kina tersebut berhasiltumbuhdan berkembang pada medium sama yangdiberi IAA 5 – 10 mg/L dikombinasikan denganIBA 0,5 mg/L. Hasil penelitian menunjukkanbahwa tingkat multiplikasi tunas aksiler lebihtinggi dari pada tunas apikal. Multiplikasi tunasaksiler menghasilkan jumlah tunas rata-ratatertinggi sebesar 24,6 tunas per eksplan padaperlakuan BA 3 mg/L sedangkan multiplikasitunas apikal tertinggi sebesar 17,2 tunas pereksplan pada perlakuan BA 5 mg/L pada umurdelapan minggu. Frekuensi pengakaran planletkina tertinggi mencapai 90% pada perlakuan IAA10 mg/L yang dikombinasikan dengan IBA 0,5mg/L. Planlet yang dihasilkan telah berhasildiaklimatisasi dan dipindahkan ke tempatpersemaian lapang.